DEVELOPMENT OF A PROPOSED ELECTIVE COURSE IN BICOL LITERATURE - VELEZ, MARIA (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study documented the development of a proposed elective course in Bicol Literature. These learning experiences were organized using Active Learning Strategies and Communicative Language Teaching strategies that allowed the students to work collaboratively with others, utilize technology and other social media platforms and be able to use English confidently and their local language judiciously. In the evaluation part of the course, the objectives of the course and the interests and needs of the students were considered along with the competencies that were expected from them. In conclusion, the interests and needs of the students are influenced by their ability to complete tasks, the competencies needed in their future careers, and to be appreciated or recognized through technology and social media platforms. Further, in formulating objectives, selecting content and learning activities, and organizing the content and learning experiences for a course, the years of experience of the teachers are reliable since they understand the interests of the students as well as the expected competencies, and school policies. Moreover, to engage the students in the content, the strategies must also be aligned with their interests, needs, and cognitive level.